INVESTIGAÇÃO DO POTENCIAL ANTIMICROBIANO DE UMA FRAÇÃO DE UM KEFIR - ANTOLIM PENHA MARTINEZ JUNIOR (2024)
Introduction - Kefir is a low-cost fermented beverage produced by grains composed of a symbiotic association of bacteria and yeasts. Studies have already demonstrated that isolated compounds from the beverage have already show that kefir fermented beverage has biological activity in various fields. With the growing threat of antimicrobial resistance, kefir emerges as a cheap and sustainable option for exploring new biomolecules with antimicrobial potential. Objective - evaluate the antimicrobial activity of a fraction of the fermented beverage from milk kefir and analize the protein profile. The fermented beverage was centrifuged in 4 steps, the first one at 18000 RPM and the subsequent 3 centrifugations were carried out with protein concentration filters based on molecular weight (30, 10, and 3 kDa) at 7500 RPM. The supernatant of the kefir from the first centrifugation step, the fraction with the highest protein concentration, was subjected to acrylamide gel electrophoresis, and the identified protein bands had their N-terminal region sequenced. The antimicrobial activity of the protein concentrate resulting from the centrifugation process using molecular weight cut-off filters (<3 kDa) was evaluated against gram-positive and gram-negative bacterial strains through minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) assays. The mechanism of action of the <3 kDa protein concentrate was evaluated with the aid of the fluorescent marker Sytox Green. This fraction was also evaluated by ultra-high performance liquid chromatography and mass spectrometry. Results - From the first fraction isolated from kefir, the N-terminal sequence of 2 protein bands purified by gel electrophoresis was obtained, with 14 and 22 residues respectively, which showed no similarity to others already published. The <3kDa protein fraction demonstrated broad-spectrum activity against the evaluated bacterial species, with minimum inhibitory concentrations and minimum bactericidal concentrations ranging from 25 to 100 mg/mL. The mechanism of action through membrane damage of this fraction was confirmed by Sytox Green. Through accurate mass evaluation by mass spectrometry, the presence of peptide molecules was constated in this fraction, and it is possibly responsible for the observed microbial action. Conclusion - These results support the efficacy of kefir against microorganisms and reinforce its probiotic potential and a source of molecules with bioactive potential.